Comparison of Mean Time Required to Achieve Sedation in Patients Undergoing Surgery in Spinal Anaesthesia Treated with Propofol vs. Midazolam - Maham Afzal Rana, Tooba Shafiq, Hina, Muhammad Athif Akram, Afshan Nisar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the mean time required to achieve sedation in patients undergoing surgery in spinal anaesthesia treated with propofol vs. midazolam. Study Design: It was a randomized controlled trial Setting: Research was conducted at Department of Anesthesiology Lahore General Hospital, Lahore from 12/03/2020 to 11/09/2020. Materials and Methods: This study involved 60 patients of both genders aged between 18-60 years belonging to ASA class I and II undergoing spinal anesthesia for groin surgery which were randomly divided into two treatment groups. Patients in Group-P received propofol while those in Group-M received midazolam for sedation. Outcome variable was mean time to sedation which was noted in minutes from the moment of administration of drug till the patient achieved sedation score of 4. Results: The mean time to sedation was significantly shorter in patients receiving propofol as compared to midazolam (4.30±1.24 vs. 7.57±2.19 minutes; p-value<0.001). Similar significant difference was observed between the groups across various subgroups based on patient’s age, BMI, diabetic and ASA status. Conclusion: In the present study, propofol was found superior to conventional practice of midazolam in terms of significantly shorter mean time to achieve sedation in patients undergoing groin surgery under spinal anesthesia which along with its well established safety profile advocates the preferred use of propofol to relieve patient’s anxiety in future anesthetic practice.